2015
DOI: 10.1007/s00170-015-7606-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing die corner accuracy through trim cut in WEDM

Abstract: Wire electrical discharge machining (WEDM) is one of the promising methods to produce precision dies and machine tools. In the present work, die corner accuracy achievable through trim cutting operation has been analyzed in the presence of a higher wire lag arising due to the higher workpiece thickness, acute corner angle, and higher flushing nozzle height. The influence of the corner error (uncut area left between the actual profile and the desired profile) generated in the first cut (rough cut) on the consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Degraded surface adversely affects mechanical properties such as fatigue strength, corrosion and wear resistance [12]. Therefore, multi-cut strategy is recommended in consideration of appropriate discharge energy, wire tension, wire feed and wire offset to eliminate surface and sub-surface defects [13][14][15]. Schematic representation of multi-cut strategy is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Degraded surface adversely affects mechanical properties such as fatigue strength, corrosion and wear resistance [12]. Therefore, multi-cut strategy is recommended in consideration of appropriate discharge energy, wire tension, wire feed and wire offset to eliminate surface and sub-surface defects [13][14][15]. Schematic representation of multi-cut strategy is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1. Selvakumar et al [21] already discussed the terminology dimensional shift (DS) which is the distance between the actual job profile and the path of rough cut (first cut). It is clearly indicated in Fig.…”
Section: Methods: Basics Of Trim Cuttingmentioning
confidence: 99%
“…During the rough cut, poor surface integrity and corner accuracy are a major concern which in turn reduces fatigue and corrosion properties of the WEDMed materials. By employing multi-pass cutting (i.e., one rough cut followed by multiple trim cut), it is possible to achieve better corner accuracy and surface integrity characteristics [19][20][21]. Despite few literatures [10,18] on WEDM of AA5083, no research work has been reported on the multipass cutting of AA5083 alloy in WEDM process.…”
Section: Introductionmentioning
confidence: 99%
“…A significant contribution was made by Selvakumar et al to achieve high corner accuracy during WEDM of Monel 400 alloy by using pulse parameter modification strategy 8 and trim cutting operation. 9 In view of enhancing corner accuracy, Sanchez et al 5 conducted experimental investigations based on the applications of path modification and cutting regime modification strategies. But, the work done by Selvakumar et al 8 concluded that the cutting regime modification strategy has some limitations and is not efficient enough to improve the corner accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…But, the work done by Selvakumar et al 8 concluded that the cutting regime modification strategy has some limitations and is not efficient enough to improve the corner accuracy. By considering corner accuracy, a few researchers 3,7,9 have reported work on multi-pass cutting in WEDM.…”
Section: Introductionmentioning
confidence: 99%